Os saberes de uma professora e sua atuação na classe hospitalar: estudo de caso no Hospital Universitário de Santa Maria - Pereira, Michele Quinhones (2006)
Teaching in hospitals ensures the study continuity as well as it performs a fundamental role in the hospitalized students recovery. I show up that hospital is not locus of education professionals. In this context, the educator that acts in the hospital environment needs education to act in this pedagogical quotidian of so different practices. However, I understand that it is essential to rethink teacher s performance in a conception that goes beyond the academic one, valuing aspects of both their personal and professional history. Faced with this reality, the research aim was to investigate the knowledge that direct teacher s work in the hospital class from Hospital Universitário de Santa Maria - HUSM, to verify knowledge produced by the practice of teachers from hospital class by taking into account their professional experiences; and, to identify how the knowledge that constitutes hospital class teacher s practice contribute to education of teachers from this area. The technique of data collection was life history by emphasizing the interviewed teacher s own history, semi-structured interview and participant observation in order to have the answer to both the research problem and the study. This research is characterized by descriptive and qualitative investigation and its methodological focus is on case study. Faced with the data interpretation, I noted that teacher s knowledge influences the development of this educational practice determinably. Therefore, I understand that pre-professional experiential knowledge constitutes the hospital class practice contributing to teacher s education to act in this area.